Revisiting the Drivers of Natural Gas Prices. A replication study of Brown & Yücel (The Energy Journal, 2008) - Gavin Roberts (International Journal for Re-Views in Empirical Economics (IREE), 2019)
This paper replicates the analysis in the paper 'What Drives Natural Gas Prices?" by Stephen P.A. Brown and Mine K. Yücel. The replication confirms the results of that analysis: a long-run relationship existed between natural-gas prices and crude-oil prices during the period from June 1997 to June 2007. This relationship was primarily driven by crude-oil prices, as natural-gas prices adjusted to deviations from the long-run relationship. Controlling for exogenous covariates related to weather, seasonality, and supply disruptions strengthen the price relationship between these two commodities. When the sample is expanded to include data generated as recently as June 2017, evidence of the long-run relationship disappears completely. I posit that this results from increased U.S. natural-supply associated with the 'shale revolution'.
https://doi.org/10.15456/iree.2018197.145241
Keywords: D72; F18; F59; Q56; 330; energy; crude oil; natural gas; cointegration; replication study